SEAWALL AND GROIN PLANNING AT KAJIMA RESORT OF JIMBARAN AREA - WIJAYA, WINDYA
The island of Bali as a domestic and international tourist destination encourages the needs for better structure of accommondation and tourist attraction. Kajima Resort is one from many example form of development of Jimbaran Beach Area, Bali. Kajima Resort which has a coastal area in their development master plan must able to meet the construction standard criteria by the law. The coastal planning should pay attention to the security of tourists and the change of the beach itself does not damage the surrounding environment. In the planning of Kajima Resort, seawall will be built to withstand damages from wave that are also useful as retaining walls with additional public facilities load. While the construction of groynes is also necessary to defend the coast from abrasion and sedimentation caused by waves and currents. The overall planning and design is largely determined by hydro Ã‚Â– oceanography aspect, ranging from building layout to building design dimensions. Geotechnical and structural aspects is necessary in the detail design of seawall dimensions.